Special Aspects of Languages - (:unkn) unknown (My University, 1994)
Spatial Aspects of Language is essentially a collection of some of the papers of the seminar on 'Spatial dimensions of language and linguistic communication in India'. The seminar was organized with a view to explore and highlight the spatial dimensions of language, speech communities, and linguistic communication in India.
Keywords: English